Iron(III)‐Catalyzed C–H Functionalization: ortho‐Benzoyloxylation of N, N‐Dialkylanilines and Its Application to 1, 4‐Benzoxazepines1. Issue 35 (30th October 2014) - Chiranjeevi, Barreddi; Vinayak, Botla; Parsharamulu, Thupakula; PhaniBabu, Vemulapalli S.; Jagadeesh, Bharatam; Sridhar, Balasubramanian; Chandrasekharam, Malapaka
Abstract: A C–O bond‐formation reaction that proceeds through C–H functionalization of N, N ‐dialkylanilines at the ortho ‐position is presented. The iron‐catalyzed selective ortho ‐benzoyloxylation follows a polar Friedel–Crafts‐like mechanism and is sensitive to the nucleophilicity of the anilines. The benzoyloxylation of a variety of N, N ‐disubstituted anilines and N ‐phenyl heterocycles is carried out under extremely mild conditions. Furthermore, the methodology has been successfully employed for the generation of 1, 4‐benzoxazepines and o ‐aminophenols. Abstract : An iron‐catalyzed C–O bond‐formation reaction that proceeds through C–H functionalization of N, N ‐dialkylanilines at the ortho ‐position is presented. The reaction is carried out under extremely mild conditions. The methodology has been successfully employed for the generation of 1, 4‐benzoxazepines and o ‐aminophenols.